Organizational Ethics Programs and the Law - Spielman, Bethany (Cambridge quarterly of healthcare ethics, 2000)
Max Weber, the grandfather of organizational theory, recognized the close association between health care organizations and law. When he introduced the concept of a legal–rational bureaucracy, he used hospitals and clinics to illustrate it. Today, there is little doubt that healthcare organizations are “law-saturated,” if not always fully compliant with the law. Like Weber's legal–rational bureaucracies, healthcare organizations have highly formalized rules and procedures. They pay a great deal of attention to legal criteria in decisionmaking, and some have entire departments devoted to legal risk management.